Perbandingan Granular Starch Hydrolyzing Enzyme dengan Glukoamilase Pada Proses Sakarifikasi Konvensional Pati Casava untuk Memproduksi Etanol - Hargono .; Andri Cahyo Kumoro; Bakti Jos (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
In a conventional cassava starch is converted into dextrins using liquefaction enzymes at high temperatures(90–120°C) during a liquefaction step. Dextrins are hydrolyzed into sugars using saccharification enzymesduring a simultaneous saccharification and fermentation (SSF) step. Recently, a granular starch hydrolyzingenzyme (GSHE), Stargen 002, was developed that converts starch into dextrins at low temperatures (30°C) andhydrolyzes dextrins into sugars during SSF. In this study, cassava starch using GSHE enzyme was comparedwith glucoamylase of commercial saccharification enzyme. Cassava starch processes for GSHE andglucoamylase treatments were performed at the same process conditions except for the saccharification step(60°C). For GSHE and glucoamylase treatments, ethanol concentrations at 72 hr of fermentation were 12.3,12.8% (v/v), respectively. Sugar profiles for the GSHE treatment were different from glucoamylase treatments,especially for reducing sugar. During SSF, the highest reducing sugar concentration for GSHE treatment was8% (w/v), whereas for glucoamylase treatments, reducing sugar concentrations had maximum of 15% (w/v).